REPRODUKSI PEMAHAMAN DAN DINAMIKA PSIKOLOGIS PAHAM RADIKAL: ANALISIS TERHADAP SIKAP ‘MENYALAHKAN’ KELOMPOK LAIN - Ahmad Saifuddin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
The study aims to find out the psychological dimension of Islamic radical group attitudes which are easily ‘blaming’ the other group that having different idea from his group. Based on the observation method to the individual that having religious radical understanding (especially to the individual/group that usually blaming the other group that having different understanding, as heresy (bid’ah), syirik, infidel (kafir), and deviate) on the range year of 2008 – 2017, which then comprehend with the various literatures correlated to the main problem of research, the study revealed that Islamic radical group having psychological problem in term of their mindset and perception, which then affected to their attitudes and behaviors. Hereby, in the certain level those psychological problems directed them to the violent actions.